Quantum coherent transport and electron–electron interaction in BiSbTe3 single crystals. (December 2022) - Rajput, Indu; Baral, Sonali; Dasoundhi, Mukesh Kumar; Kumar, Devendra; Lakhani, Archana
Abstract: This report focuses on the role of defects on magnetotransport properties of the single crystal of BiSbTe 3 topological insulator. Two cleaved crystals S1 and S2 of the same boule have been used, among them, S1 shows metallic behavior whereas S2 represents the multiple transport mechanism which includes thermal activation behavior, hopping conduction of localized charge carriers, quantum coherent transport and electron–electron interaction at high, moderate and low temperatures respectively. The detailed resistivity and magnetoresistance analysis confirm the presence of weak antilocalization behavior explained by Hikami-Larkin-Nagaoka formula. These crystals indicate the presence of multichannel quantum coherent transport which depends on the thickness of sample. Graphical abstract: